Posterior reversible encephalopathy syndrome: differences between pregnant and non-pregnant patients - Luiz Carlos Porcello Marrone; Giovani Gadonski; Luciano Passamani Diogo; João Pedro Farina Brunelli; William Alves Martins; Gabriela de Oliveira Laguna; Laura Fuchs Bahlis; João Rubião Hoefel-Filho; Bartira Ercilia Pinheiro Da Costa; Carlos Eduardo Poli-; Antônio Carlos Huf Marrone; Jaderson Costa Da Costa (MDPI AG, 2014)
Posterior reversible encephalopathy syndrome (PRES) is a clinical-radiologic entity not yet understood, that presents with transient neurologic symptoms and particular radiological findings. Few papers show the differences between pregnant and non-pregnant patients. We review the cases of 38 women diagnosed with PRES, in order to find significant differences between pregnant (18) and non-pregnant (20) patients. We found differences among the age of patients (25.83 years old in pregnant and 29.31 years old in non pregnant; P=0.001); in the mean of highest systolic blood pressure, that was higher in non-pregnant group (185:162 mmHg; P=0.121); and in creatinine levels that was higher in non-pregnant group (3.47:1.04 mg/dL; P=0.001). To our knowledge, just a few papers analyzed whether PRES syndrome presented in the same way in pregnant and non-pregnant patients. The differences and the possible pathophisiology of this syndrome still remain enigmatic.